البعثات التعليمية السعودية إلى جامعات الولايات المتحدة: دراسة تاريخية - البشر، سعود غسان أحمد (كلية الامارات للعلوم التربوية, 2023)
تتميز مؤسسات التعليم العالي في الولايات المتحدة الأمريكية بالسمعة الحسنة والجودة الأكاديمية؛ إذ تتصدر الجامعات الأمريكية دائما التصنيفات التعليمية لأفضل مؤسسات التعليم العالي في العالم. وتتميز الجامعات الأمريكية بالتنوع الثقافي وتمثيل كبير من الطلاب الدوليين، حيث يشكل الطلاب الدوليون قرابة 5% من مجموع عدد الطلاب في مؤسسات التعليم العالي في الولايات المتحدة، ويشكل الطلاب الدوليون من المملكة العربية السعودية جزءا كبيرا من مجموع الطلاب الدوليين في مؤسسات التعليم العالي في أمريكا، وقد جاء الطلاب السعوديون الدوليون كأكبر رابع مجموعة من الطلاب الدوليين في هذه الدولة. وتهدف الدراسة إلى اكتشاف أهم الحقائق والإحصائيات والتفاصيل التاريخية المرتبطة بتاريخ البعثات السعودية إلى الولايات المتحدة منذ العقد الرابع من القرن الميلادي الماضي، والذي شهد أول دفعة من الطلاب السعوديين الدارسين في الولايات المتحدة وحتى عام 2021. وقد استخدم الباحث المنهج التاريخي لمناسبته أهداف الدراسة. Their excellent reputation and academic quality distinguish higher education institutions in the United States of America, as American universities always lead the educational rankings of the best higher education institutions in the world. American universities are characterized by cultural diversity and a significant representation of international students, as international students constitute approximately 5% of the total number of students in higher education institutions in the United States. International students from the Kingdom of Saudi Arabia make up a large part of the total number of international students in higher education institutions in America. Saudi international students came as this country's fourth largest group of international students. The study aims to discover the most important facts, statistics, and information related to the history of Saudi missions to the United States from the fourth decade of the last century until 2021. The researcher used the historical method to suit the objectives of the study.
Keywords: البعثات التعليمية -- مؤسسات التعليم العالي -- الجامعات الأمريكية -- الطلبة السعوديين